A Machine Learning Approach for the Automatic Classification of Schizophrenic Discourse - Allende-Cid, H. (IEEE Explore, 2020)
Schizophrenia is a chronic neurobiological disorder whose early detection has attracted signi cant attention from the clinical, psychiatric, and also arti cial intelligence communities. This latter approach has been mainly focused on the analysis of neuroimaging and genetic data. A less explored strategy consists in exploiting the power of natural language processing (NLP) algorithms applied over narrative texts produced by schizophrenic subjects. In this paper, a novel dataset collected from a proper eld study is presented. Also, grammatical traits discovered in narrative documents are used to build computational representations of texts, allowing an automatic classi cation of discourses generated by schizophrenic and non-schizophrenic subjects. The attained results showed that the use of the proposed computational representations along with machine learning techniques enables a novel and precise strategy to automatically detect texts produced by schizophrenic subjects.